Scientific rationale for the use of a mucogingival gel in the comprehensive treatment of generalized periodontitis in military personnel and veterans (literature review) - Kopchak , O.V.; Berehovyi , O.O.; Asharenkova, O.V.; Obolonska, H.O.; Yanishevskyi , K.A. (Medicni Perspektivi, 2025)
The current level of national defense security requires enhanced standards for the health and professional reliability of military personnel. In this context, oral health is considered a key factor influencing the performance of official duties, well-being, and quality of life. It can be asserted that optimizing the treatment of periodontal pathology in military personnel is not only an element of maintaining general health but also a part of the strategic orientation of any country. However, therapeutic approaches to generalized periodontitis often demonstrate low effectiveness, with only a temporary stabilizing effect on disease progression. The aim of this study is to evaluate the effectiveness of available local treatment options in controlling chronic periodontitis, with or without concurrent mechanical debridement by scaling. A total of 77 English- and Ukrainian-language scientific sources published between 2006 and 2025 were analyzed, selected based on relevance, presence of empirical data, and methodological quality. The literature search was conducted using the electronic catalog of the National Scientific Medical Library of Ukraine and databases such as Google Scholar, PubMed, and Scopus. The analysis focused on the effectiveness of various groups of local drug formulations, with special attention to gels exhibiting antibacterial, anti-inflammatory, antioxidant, and mucoadhesive properties. Mucogingival gels were found to ensure stable delivery of active components without systemic load, reduce periodontal pocket depth, bleeding, swelling, and promote tissue regeneration. The highest clinical efficacy was demonstrated by gels containing chlorhexidine, metronidazole, doxycycline, statins, and phytocomponents. Their use is recommended at all stages of treatment, including supportive therapy. The results of the literature review confirm the potential of mucogingival gel in the comprehensive treatment of generalized periodontitis, substantiating its application for military personnel and veterans.